(untitled) (Revista Archai, 2022)
In the first two sections of this paper, I present some of the arguments that the Buddhist Indian philosophers Nagarjuna (second/third century) and Vasubandhu (fourth/fifth century) use to show the logical untenability of the phenomena of motion and of the existence of multiple external/extramental objects. The logic of these arguments seems to be quite comparable – and actually, within contemporary buddhological studies, it was sometimes compared – to the one that Zeno of Elea uses in his paradoxes against motion and multiplicity. However, in the third section, I try to show that the most immediate philosophical purposes of these three thinkers diverge and are irreconcilable. While Zeno criticizes motion and multiplicity in order to show the plausibility of the attributes of motionlessness and uniqueness of Parmenides’ Being, Nagarjuna and Vasubandhu’s paradoxes should be understood within philosophical projects that, in tune with the Buddha’s teaching of the “middle way”, try to keep themselves equidistant from the categories of “being” and “non- being”, avoiding both. Finally, in the fourth and last section, I defend the thesis that the ultimate purposes of the Eleatics’ view and those of the two Buddhist philosophers are, once again, comparable. Both Parmenides and the Buddha, as well as their respective epigones, try to promote an “epistemic revolution”, in their followers, which consists in the shift from the ordinary vision of reality to an extraordinary or supreme understanding, coincident with reality in itself and, therefore, ultimately true.